S100A4 expression is a prognostic indicator in small intestine adenocarcinoma. Issue 3 (23rd September 2013) - Roh, Jin; Knight, Spencer; Chung, Joon-Yong; Eo, Soo-Heang; Goggins, Michael; Kim, Jihoon; Cho, HyungJun; Yu, Eunsil; Hong, Seung-Mo
Abstract : Aims: Due to the rarity of small intestine adenocarcinoma (SIAC), estimating the prognosis for patients with surgically resected SIAC is difficult. Overexpression of S100A4 has been linked to worse patient survival in several malignant neoplasms, but its significance in SIAC has not been determined. Methods: S100A4 protein expression was assessed in 197 surgically resected SIAC cases and compared with clinicopathological factors, including patient survival. Results: A progressive increase in S100A4 labelling was observed in normal intestinal epithelium, adenoma and adenocarcinoma (p<0.001), and 50 SIAC cases (26.2%) showed strong S100A4 expression. Patients with SIAC with strong S100A4 expression had a higher pT classification (p=0.05), as well as increased lymph node metastasis (p=0.009) and perineural invasion (p=0.002). Patients with SIAC with strong S100A4 expression had significantly worse survival (median survival, 21 months) than those with weak/no S100A4 expression (42.5 months) by univariable (p=0.04) and multivariable (p=0.01) analyses. Conclusions: S100A4 overexpression is observed in a subset of SIACs, is associated with advanced disease and can be used as a prognostic indicator of poor prognosis in patients with SIAC.